2014
DOI: 10.3390/cryst4030209
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Frequency Generation in Quasi-Periodic Stacks of Nonlinear Dielectric Layers

Abstract: Three-wave mixing in quasi-periodic structures (QPSs) composed of nonlinear anisotropic dielectric layers, stacked in Fibonacci and Thue-Morse sequences, has been explored at illumination by a pair of pump waves with dissimilar frequencies and incidence angles. A new formulation of the nonlinear scattering problem has enabled the QPS analysis as a perturbed periodic structure with defects. The obtained solutions have revealed the effects of stack composition and constituent layer parameters, including losses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The interest to this topic is connected with the fact that the mixing process in the nonlinear artificial structures can be controlled not by only tailoring the coherence and localisation of the interacting waves but also by altering independently the intensity and phasing of individual pump waves [9]. In earlier studies, it was demonstrated that CFG by two pump waves of frequencies   and   , incident at dissimilar angles, offers additional degrees of freedom in controlling the frequency mixing process and spectrum [10]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…The interest to this topic is connected with the fact that the mixing process in the nonlinear artificial structures can be controlled not by only tailoring the coherence and localisation of the interacting waves but also by altering independently the intensity and phasing of individual pump waves [9]. In earlier studies, it was demonstrated that CFG by two pump waves of frequencies   and   , incident at dissimilar angles, offers additional degrees of freedom in controlling the frequency mixing process and spectrum [10]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been already demonstrated that the second harmonic generation enhancement at the band edges is noticeably impaired by the higher losses of the pump wave that reduce the overall conversion efficiency 5 . In refs 6 , 7 it was shown that the combined effect of the pump wave dissipation and attenuation of the mixing products passing through the periodic and quasi-periodic stacks of binary layers of anisotropic nonlinear dielectrics causes dramatic reduction of the CFG efficiency. One way to mitigate this problem is to use the active materials, so that to compensate the losses with the gain of active media.…”
mentioning
confidence: 99%